2007
DOI: 10.1158/0008-5472.can-06-4607
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G1 Is a Target of miR-122a, a MicroRNA Frequently Down-regulated in Human Hepatocellular Carcinoma

Abstract: We investigated the role of microRNAs (miRNAs) in the pathogenesis of human hepatocellular carcinoma (HCC). A genome-wide miRNA microarray was used to identify differentially expressed miRNAs in HCCs arisen on cirrhotic livers. Thirty-five miRNAs were identified. Several of these miRNAs were previously found deregulated in other human cancers, such as members of the let-7 family, mir-221, and mir-145. In addition, the hepato-specific miR-122a was found downregulated in f70% of HCCs and in all HCC-derived cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
617
6
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 757 publications
(664 citation statements)
references
References 50 publications
33
617
6
8
Order By: Relevance
“…32-34 miR-141 is associated with various types of cancer. [35][36][37][38][39] Given that miR-141 was found to be either upregulated (ovarian and colorectal cancers) 35,36 or downregulated (prostate, hepatocellular and renal cell carcinoma) [37][38][39] in various cancers, it appears that miR-141 might have different roles, as either an oncogene or as a tumor-suppressor gene, in different cancer types of cancer. Therefore, most of the differentially expressed miRNAs identified in this study by comparing miRNA expression in cisplatinsensitive and -resistant human ESCC cell lines appear to show some involvement in cancer; however, none of these miRNAs has previously been found to be associated with the development of cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32-34 miR-141 is associated with various types of cancer. [35][36][37][38][39] Given that miR-141 was found to be either upregulated (ovarian and colorectal cancers) 35,36 or downregulated (prostate, hepatocellular and renal cell carcinoma) [37][38][39] in various cancers, it appears that miR-141 might have different roles, as either an oncogene or as a tumor-suppressor gene, in different cancer types of cancer. Therefore, most of the differentially expressed miRNAs identified in this study by comparing miRNA expression in cisplatinsensitive and -resistant human ESCC cell lines appear to show some involvement in cancer; however, none of these miRNAs has previously been found to be associated with the development of cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The global miRNA expression analyses (hierarchical clustering and principal component analysis) showed that the expression profiles of the miRNAs differed between the cisplatin-sensitive and -resistant cell lines (Figure 2), and expression levels of 45 miRNAs were changed by more than fourfold in cisplatin-sensitive cell lines as compared with cisplatin-resistant cell lines (Supplementary Table 1). Subsequently, the expression levels of the 10 miRNAs that were selected according to the miRNA microarray data and literature search [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were validated by quantitative reverse transcription-PCR. This confirmed that miR-141, miR-21, miR-19b, miR-200a, miR-19a, miR-27a, miR-20a and miR-20b were expressed at significantly higher levels in the cisplatinresistant lines, and miR-205 and miR-224 at significantly lower levels than in the cisplatin-sensitive cell lines (Po0.05) (Table 1).…”
Section: Cisplatin-sensitive and -Resistant Human Escc Cell Linesmentioning
confidence: 99%
“…Elles comprennent les hyperplasies nodulaires REVUES au fonctionnement hépatique, il est sous-exprimé dans la majorité des CHC. Récemment, une de ses cibles impliquée dans la régulation du cycle cellulaire, la cycline G1, a été validée expérimentalement dans un modèle cellulaire d'hépatocytes [25]. Par ailleurs, l'observation d'une sous-expression de miR-122 à la fois dans les CHC et les tumeurs bénignes suggère que la dérégulation de miR-122 serait liée à des évènements précoces de tumorigenèse [19].…”
Section: Les Tumeurs Hépatocellulaires : Une Grande Diversité De Lésionsunclassified
“…Depuis 2005, une dizaine d'études globales de l'expression des miARN dans les CHC a été publiée (Tableau 1) [19][20][21][22][23][24][25][26][27][28]. Varnholt et al ont montré dans une méta-analyse récente que les résultats de ces diffé-rentes études étaient assez peu concordants [29].…”
Section: Altérations De L'expression Des Miarn Dans Les Chcunclassified
“…With DNA microarray assay, several signaling pathways are potentially involved in HCC development and progression through the modulation of multiple mRNAs (Gramantieri et al, 2007). The NF-kB-inducing kinase (NIK) is a member of mitogen-activated protein kinase kinase kinase (MAP3K) family that potently participates in the activation of nuclear factor kB (NF-kB), a family of eukaryotic transcription factors that mediate cell growth and transformation.…”
Section: Introductionmentioning
confidence: 99%